2019
DOI: 10.1103/physrevaccelbeams.22.071003
|View full text |Cite
|
Sign up to set email alerts
|

Validation of energy deposition simulations for proton and heavy ion losses in the CERN Large Hadron Collider

Abstract: shower simulations are essential for understanding and predicting the consequences of beam losses in high-energy proton and ion colliders. Shower simulations are routinely used at CERN for estimating the beam-induced energy deposition, radiation damage, and radioactivity in the Large Hadron Collider (LHC). Comparing these shower simulations against beam loss measurements is an important prerequisite for assessing the predictive ability of model calculations. This paper validates FLUKA simulation predictions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…This number of tracks is similar to the observations within statistical uncertainties. It is worthwhile pointing out that the statistical error is smaller than the combination of the uncertainties on input fluxes on the order of 10% on the basis of our previous experience with LISA Pathfinder (Grimani et al 2019) and the intrinsic Monte Carlo resolution also on the order of 10% (Lechner et al 2019). While the detector does not allow us to distinguish different particle species, the simulations indicate that for primary protons the particles traversing the sensitive part of the detector in particle numbers to the total number down to 1% in composition are: 80% protons, 17% electrons and positrons, and 3% pions.…”
Section: Comparison Of Simulations and Cosmic-ray Observations In The Metis Visible Light Imagesmentioning
confidence: 93%
“…This number of tracks is similar to the observations within statistical uncertainties. It is worthwhile pointing out that the statistical error is smaller than the combination of the uncertainties on input fluxes on the order of 10% on the basis of our previous experience with LISA Pathfinder (Grimani et al 2019) and the intrinsic Monte Carlo resolution also on the order of 10% (Lechner et al 2019). While the detector does not allow us to distinguish different particle species, the simulations indicate that for primary protons the particles traversing the sensitive part of the detector in particle numbers to the total number down to 1% in composition are: 80% protons, 17% electrons and positrons, and 3% pions.…”
Section: Comparison Of Simulations and Cosmic-ray Observations In The Metis Visible Light Imagesmentioning
confidence: 93%
“…Although the fluences cannot be directly measured with BLMs, the FLUKA particle transport software [12], [13] enables us to perform simulations that can be later scaled with the BLM's TID measurements in order to retrieve fluences. For benchmarked regions, agreement between FLUKA simulations with the implemented BLMs and BLM measurements is better than 40% [14].…”
Section: ) Beam Loss Monitorsmentioning
confidence: 95%
“…The predictive ability of the FLUKA code for BLM response studies in the LHC radiation environment has been demonstrated in Ref. [40]. In the following, we use this simulation technique for reproducing dust-induced signal patterns recorded during 6.5 TeV operation in run II.…”
Section: Reconstruction Of Dust-induced Beam Losses In the Lhc Arcsmentioning
confidence: 99%